Remarkable new species of epedanid from Vietnam (Arachnida: Opiliones: Laniatores: Epedanidae) - Tchemeris, Aleksey N. (Zootaxa, 2020)
The genus Euepedanus of the family Epedanidae is recorded from Vietnam for the first time. Euepedanus vietnamicus sp. nov. (males and females) is diagnosed, figured and described. The main characteristics that distinguish this species from other species Euepedanus are quite large body sizes, structure of the distal segment of the chelicerae, armament of palps and on the dorsal surface of body with a pattern resembling the Latin letter X. The only known locality of the new E. vietnamicus sp. nov. in southern Vietnam, is mapped.